2000
DOI: 10.1093/humrep/15.10.2093
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial to evaluate the efficacy of a vaginal ring releasing progesterone for IVF and oocyte donation

Abstract: A polysyloxane vaginal ring containing 1g of natural progesterone was developed as luteal supplementation for women treated with IVF-embryo transfer and for agonadal women participating in an oocyte donation programme. The ring provides continuous release of progesterone (10-20 nmol/l) for 90 days. The efficacy of this form of progesterone supplementation was evaluated in two multicentre prospective randomized trials. IVF-embryo transfer trial: After oocyte aspiration, 505 women were randomly allocated to prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…The clinical pregnancy rates for the P vaginal ring were 36.6% and 39.8% for fresh IVF and fresh oocyte donation, respectively, as compared with 36.6% and 28.6% for the standard IM protocol for fresh IVF and fresh oocyte donation, respectively (13).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The clinical pregnancy rates for the P vaginal ring were 36.6% and 39.8% for fresh IVF and fresh oocyte donation, respectively, as compared with 36.6% and 28.6% for the standard IM protocol for fresh IVF and fresh oocyte donation, respectively (13).…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, this was the first use of a P vaginal ring in the United States for luteal support, although researchers in other countries have evaluated similar P-releasing rings in IVF and donor oocyte candidates (13,14). The primary objective of this phase II pilot study was to evaluate, in women with clinical or medically induced agonadism, the rates of adequate endometrial transformation with a P vaginal ring or a P vaginal gel in donor oocyte recipients.…”
mentioning
confidence: 99%
“…The clinical pregnancy rates for the VR progesterone in the study by Zegers-Hochchild et al were 36.6 and 39.8 % for fresh IVF and fresh oocyte donation, respectively. In the same study, the clinical pregnancy rates are reported as 36.6 and 28.6 % for the standard IM protocol for fresh IVF and fresh oocyte donation, respectively [29].…”
Section: Progesterone Vaginal Ring For Luteal Supportmentioning
confidence: 88%
“…A RCT performed in South America compared the vaginal progesterone ring to intramuscular progesterone for use in both IVF and oocyte donation cycles. They report an increased, but not significant clinical pregnancy rate and statistically significant increased implantation rate with the vaginal ring (VR) [29]. The clinical pregnancy rates for the VR progesterone in the study by Zegers-Hochchild et al were 36.6 and 39.8 % for fresh IVF and fresh oocyte donation, respectively.…”
Section: Progesterone Vaginal Ring For Luteal Supportmentioning
confidence: 96%
“…In the other trial, the study was conducted in oocyte recipients, and the ring proved to be associated with a better implantation rate (37).…”
Section: Intramuscular and Vaginal Progesteronementioning
confidence: 99%